(untitled) (Journal of Partial Differential Equations, 2022)
Denote K _ψ, θ (Ω) ={ vW^1,p (Ω) : vψ, a.e. and v-θ W_0^1,p (Ω) }, where ψ is any function in Ω R^N, N2, with values in R {± ∞} and θ is a measurable function. This paper deals with global integrability for u K_ψ, θ such that _Ω A (x, abla u), abla (w-u) dx _Ω F, abla (w-u) dx, w K_ψ,θ (Ω), with |A (x,ξ)| ≈ |ξ| ^p-1, 1